Influencia de tres concentraciones de un suplemento de péptidos en el cultivo de alevinos de gamitana Colossoma macropomum (cuvier, 1816) en tanques de concreto - Torres Petterman, Jason (2023)
The present research took place during the second half of the year 2022, whose main objective was to know the influence of a peptide supplement in the culture of gamitana fry "Colossoma macropomum" cultivated in concrete tanks in the facilities of the Panduro Fish Perú E.I.R.L. aquarium for 120 days. The DCA experimental design was used, having 3 treatments and a control, all in triplicate. Length, weight and physical and chemical parameters were measured every fifteen days, and zootechnical indexes were calculated such as: daily weight gain (DWG), specific growth rate (SGR), relative growth rate (RGR), weight variation coefficient (CVP%), condition factor (K), apparent food conversion index (FCI) and survival (S%). The concentrations administered were: T1=5ml/kg, T2=15ml/kg, T3=25ml/kg and C = 0ml/kg, of peptide supplement per kilogram of diet, the feeding frequency was twice per day. The results show that all the treatments used show significant differences (p<0.05), reaching a maximum growth value of 28.56 ± 0.05 cm in length and 397.55 ± 0.19 g in weight, in the zootechnical indexes a favorable ICAA and survival >91% are evidenced, in addition, the protein content of the diets was adequate >30% and < 35%. Finally, it is concluded that the T3=25ml/Kg shows favorable results for each parameter evaluated, in addition to a higher feed conversion rate, which allows us to mention that the cultivation of gamitana fry is profitable, using the appropriate supplement concentrations and those of lower price.